Peningkatan Kompetensi Guru Dalam Menyusun Perangkat Pembelajaran RPP Melalui Workshop: Increasing Teacher Competence in Developing RPP Learning Materials Through Workshops - Denok Arimbi (Neraca: Jurnal Pendidikan Ekonomi, 2023)
Based on the Regulation of the Minister of Education and Culture Number 6 of 2018 concerning Education and Training (Training) for Candidates for Principals is the preparation of competency for prospective school principals to strengthen insights, knowledge, attitudes, values and skills in leading schools, which aims to: (1) provide experience learning that integrates attitudes, knowledge, and skills on the dimensions of personality, managerial, entrepreneurial, supervision, and social competencies with empirical (contextual) experience according to the characteristics of prospective principals (2) develops the ability of prospective principals in identifying learning problems to improve learning outcomes learners. This research is an action research of school principals. The subjects in this study were Guppy Palangkaraya Middle School teachers. The stages of this research are planning, implementation, observation and reflection. From the results of the analysis of the ability of the teacher cycle 1 reached 95.45% and cycle 2 increased to 100%. there has been an increase of 4.55%. Competency improvement based on AKPK can improve supervisory competence of prospective school principals. The implementation of compiling RPP learning tools from home can improve student achievement.